UPACARA MARGONDANG DAN TORTOR BATAK ANGKOLA DITINJAU DARI PERSPEKTIF PENDIDIKAN ISLAM - Diana Riski Sapitri Siregar; Akhmad Sodiq; Zahruddin Zahruddin; Maftuhah Maftuhah (MUMTAZ : Jurnal Pendidikan Agama Islam, 2022)
This study aims to determine the process of presenting the margondang and tor-tor ceremony for the wedding of the Batak Angkola community and to know the view of Islamic education on the margondang and tor-tor ceremony of the wedding of the Batak Angkola community. This study uses a qualitative approach with ethnographic methods. Data collection methods used were in-depth interviews, observation and literature study. The results of this study include: 1) The process of the margondang ceremony starts from martahi ungut-ungut (family deliberation), martahi sahuta (one village deliberation), martahi godang (deliberation of the kings), after that the maralok-alok kings (customary session), then panaek gondang (hitting drums). After that began the manortor of the men, namely suhut bolon, kahanggi and anak boru, followed by the tortor of the mothers, tortor kings, tortor naposo nauli bulung, then tortor namora pule (bride). After the manortor is complete, the bride and groom are taken to the main building's butchers, and the last event is the implementation of the mangupa. 2) The view of Islamic education on the margondang and tor-tor ceremony for the wedding of the Batak Angkola community shows that the margondang has Islamic educational values ​​in each of its traditional ceremonies, such as religious values, social values ​​and moral values, so that the basis of Islamic education is the basis of religion and the purpose of Islamic education in social (ahdaf ijtima'iyyah) can be achieved in this ceremony.